Effects of pressure on lignocellulosic biomass fast pyrolysis in nitrogen and carbon dioxide. (1st March 2021) - Cerciello, F.; Apicella, B.; Russo, C.; Cortese, L.; Senneca, O.
Abstract: The present study investigates the influence of pressure on the products of fast pyrolysis of a lignocellulosic biomass (Walnut Shells). Experiments were carried out using a special heated strip reactor (HSR) at temperature of 1573 and 2073 K, pressure up to 8 bar and heating rate of 10 4 K/s. Two atmospheres have been investigated: N2 and CO2 . Increasing the pressure of heat treatment, the combustion pattern and the average combustion reactivity of the chars change remarkably. Multiple components with different combustion reactivity have been found in the char samples. Upon heat treatment in N2 the most reactive components are depleted more easily than upon heat treatment in CO2 . Consequently, thermodeactivation is more severe in N2 than in CO2 . Raman analysis of the chars shows that graphitic order develops only upon heat treatment at 2073 K at the pressure of 2 bar, but not upon heat treatment at 1573 K, not even at the higher pressure investigated (4 and 8 bar). The loss of reactivity induced by pressure is therefore ascribed to changes in the internal distribution of char components. The evolution of the solid components is accompanied by changes in the distribution of aliphatics/methoxy aromatic compounds in the produced tar. The interplay of temperature, pressure, and CO2 affects both mineral matter and the carbon matrix resulting into a rather complex behaviour.